2018
DOI: 10.1002/ejsp.2536
|View full text |Cite
|
Sign up to set email alerts
|

Why is it so hard to change? The role of self‐integrity threat and affirmation in weight loss

Abstract: People are frequently dissatisfied with their body weight. Messages alleging that lower weight is esthetically preferable, healthier, and achievable likely trigger chronic self‐integrity threat, the sense that one's personal adequacy is in doubt. We examined whether self‐integrity threat, which creates stress and pressure to restore self‐integrity, contributes to the challenges of weight and behavior change. Weight‐dissatisfied women completed in‐lab tasks including a values affirmation manipulation and two‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…These results go beyond work showing that values affirmation promotes weight stability (i.e., Logel & Cohen, 2012;Logel et al, 2018Logel et al, , 2019. There, a 15-min writing task bolstered global self-integrity, presumably buffering weightdissatisfied participants against weight-related self-integrity threats in a lab context including multiple weight-relevant activities.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…These results go beyond work showing that values affirmation promotes weight stability (i.e., Logel & Cohen, 2012;Logel et al, 2018Logel et al, , 2019. There, a 15-min writing task bolstered global self-integrity, presumably buffering weightdissatisfied participants against weight-related self-integrity threats in a lab context including multiple weight-relevant activities.…”
Section: Discussionmentioning
confidence: 57%
“…Weight-dissatisfied college women who were asked to write about identify-relevant core values lost 3.41 lbs (1.55 kg) approximately 2 months later, whereas controls had gained 2.76 lbs (1.25 kg; Logel & Cohen, 2012). Effects were subsequently replicated, primarily among higher weight women (Logel et al, 2018). More than 2 years later, affirmed higher weight women from the two studies maintained weight stability, whereas controls gained some weight (Logel et al, 2019).…”
mentioning
confidence: 92%
“…(For affirmed students, the difference score was significantly positive; M = .33, SD = .44, one‐sample t = 3.32, p = .004). Third, the few affirmation studies to include no‐task control conditions have not observed negative effects of the standard control condition used here (see Cohen et al., 2006; Logel et al., 2019).…”
Section: Discussionmentioning
confidence: 77%
“…This “worthiness” is linked to self-integrity, an individual’s sense of being “good enough”—competent enough to control important life outcomes (Steele, 1988). Threats to self-integrity, where an experience threatens one’s personal adequacy, are barriers to change for many behaviors (see e.g., Logel et al, 2019). It was clear that this was a ubiquitous experience for this sample and that going through this process was a necessary step in self-change.…”
Section: Resultsmentioning
confidence: 99%